Technical and tactical evolution of the offensive team sequences in LaLiga between 2008 and 2021. Is Spanish football now a more associative game? - González-Rodenas, Joaquín; Moreno-Pérez, Víctor; López-Del Campo, Roberto; Resta, Ricardo; Coso, Juan (Biology of Sport, 2024)
The aim of this investigation was to study the technical and tactical evolution of the offensive team sequences in the Spanish football teams from 2008/09 to 2020/21. A comparative analysis including twelve variables related to the development of offensive sequences in 4940 matches was performed from 2008/09 to 2020/21 seasons of the Spanish professional football league (LaLiga). All match observations were recorded using a validated video tracking system. Multilevel linear mixed models were used to examine the differences across seasons, considering the effects of contextual variables. The number of passes per sequence (2.4 [CI: 2.2–2.5] vs 3.2 [CI: 3.0–3.4]; +33.3%), the passing accuracy (72.1 [CI: 70.6–73.5] vs 76.9 [CI: 75.4–78.3]%; +6.8%) and the average duration of the team sequences (6.4 [CI: 5.9 6.8] vs 8.3 [CI: 7.8–8.7] seconds; +25.76%) showed a small increasing trend over the seasons ( P < 0.05). In contrast, variables such as the direct speed of progression (2.2 [CI: 2.1–2.3] vs 1.6 [CI: 1.5–1.7] metres/second; -24.5%), key passes (8.1 [CI: 7.6–8.5] vs 6.8 [CI: 6.3–7.2]; -15.8%), and the sequences that ended in the attacking third (64.8 [CI: 62,7–66.8] vs 57.1 [CI: 55.1–59.2]; -11.7%) or in a shot (13.0 [CI: 12.4–13.6] vs 10.2 [CI: 9.6–10.8]; -21.6%) showed a small decreasing trend from 2008/09 to 2020/21 ( P < 0.05). Spanish professional football teams slightly evolved technically and tactically towards a more associative style of play that includes longer passing sequences. This evolution also involved a decreasing speed of progression and fewer technical actions such as through balls, key passes and shots.